Development of teaching materials for writing fantasy story texts using book creator junior high school students - Dedi Soepandi; Ika Mustika (IKIP Siliwangi, 2026)
This study develops teaching materials for writing fantasy texts based on Book Creator using the Problem-Based Learning (PBL) model to enhance the creativity and writing skills of seventh-grade junior high school students. This research employs the Research and Development (R&D) method, encompassing needs analysis, product development, expert validation, small-scale trials, and large-scale trials. Validation results indicate that the teaching materials are highly feasible, with an average score of 86.2 based on expert and student assessments. Moreover, these materials effectively improve students’ writing skills, with a 75% increase in the experimental class compared to 38% in the control class. The strength of these teaching materials lies in the interactive features of Book Creator, which enable students to develop fantasy stories using text, images, and other multimedia elements. The implementation of the PBL model also helps students understand story structures while enhancing critical and creative thinking skills. Thus, this study concludes that Book Creator-based teaching materials with the PBL model are more effective than conventional methods in improving students’ writing skills and creativity. These findings are expected to serve as a reference for teachers in developing technology-based learning innovations in the digital era.